The Influence of Motivation and Organizational Culture on the Performance of Employees at the Department of Fisheries and Food in Pasaman Regency - Sari, Ria Widhia; Endarwita, Endarwita; Yurasti, Yurasti (CV. Proaksara Global Transeduka, 2025)
Considering the critical importance of human resources in the attainment of organizational objectives, it is imperative to scrutinize the factors that impact employee effectiveness. Following preliminary assessments and discussions, issues pertaining to motivation and the prevailing organizational climate have surfaced as prominent matters within the Department of Fisheries and Food. These elements are believed to have a significant influence on the levels of employee productivity. Consequently, this research investigates on how motivation and organizational culture affect employee performance at Pasaman Regency's Department of Fisheries and Food. Using total sampling, all 33 departmental employees comprised both the population and sample. Data collection employed a quantitative associative method, with multiple linear regression for analysis. Findings revealed motivation significantly impacts employee performance individually (p = 0.000 < 0.05). Organizational culture also demonstrates significant individual effects on performance (p = 0.000 < 0.05). Combined, both factors significantly influence employee performance (p = 0.000 < 0.05). The R² value of 0.781 shows that motivation and organizational culture account for 78.1% of performance variation among employees at the Department of Fisheries and Food in Pasaman Regency.